2020
DOI: 10.1101/2020.05.21.106914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between erythrocyte dynamics and vessel remodelling in developmental vascular networks

Abstract: Sprouting angiogenesis is an essential vascularisation mechanism and consists of two phases: sprouting and remodelling. The remodelling phase is driven by rearrangements of endothelial cells (ECs) within the primitive vascular plexus. Prior work has uncovered how ECs polarise and migrate in response to flow-induced wall shear stress (WSS). However, the question of how the presence of red blood cells (RBCs), and their profound impact on microvascular haemodynamics, affect vascular remodelling has not been addre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 91 publications
(155 reference statements)
0
7
0
Order By: Relevance
“…This tool is available and useful for the study of blood flow in low complexity network as retinas. It is worth mentioning that computational modelization of particles has just uncovered the essential role of circulating red blood cells in generating regional shear stress differences and thus in regulating vascular remodeling by modulation of blood viscosity ( Zhou et al, 2020 ). Of note, new advances in mathematical approaches in the multidisciplinary field of Adaptive Systems could also help decipher the dynamic changes of endothelial cells responding to a variety of environmental signals in order to adopt the best network architecture possible ( Bentley et al, 2014b ).…”
Section: New Methodological Approaches and Tools To Understand Capillmentioning
confidence: 99%
See 2 more Smart Citations
“…This tool is available and useful for the study of blood flow in low complexity network as retinas. It is worth mentioning that computational modelization of particles has just uncovered the essential role of circulating red blood cells in generating regional shear stress differences and thus in regulating vascular remodeling by modulation of blood viscosity ( Zhou et al, 2020 ). Of note, new advances in mathematical approaches in the multidisciplinary field of Adaptive Systems could also help decipher the dynamic changes of endothelial cells responding to a variety of environmental signals in order to adopt the best network architecture possible ( Bentley et al, 2014b ).…”
Section: New Methodological Approaches and Tools To Understand Capillmentioning
confidence: 99%
“…essential role of circulating cells, often disregarded in theoretical in silico simulations, in modulating blood viscosity and regional shear stress (Zhou et al, 2020). Moreover, the geometry of the microvascular network also influences shear stress patterns and values, particularly at curvatures and bifurcations (Chiu and Chien, 2011).…”
Section: Blood Flow Basicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its release in 2008, it has been applied to a range of physiological flow problems such as cerebral and retinal flow, vascular remodelling, and magnetic drug targeting [31], [32], [33]. Recent development efforts include integration of finite element and immersed boundary methods [34], [35] and efficient self-coupling [9]. While HemeLB is actively developed to take advantage of exascale The goal of the present work is to augment the existing MPI-parallelization of HemeLB with a CUDA kernel to leverage one or more GPUs available to an MPI process.…”
Section: B Related Workmentioning
confidence: 99%
“…Early investigations demonstrated that haematocrit (the volume fraction of RBCs in total blood) can vary between child branches of a vascular bifurcation as a function of haemodynamic and geometrical vessel properties (see [10] for a review). Our recent work has shown that vascular development works to avoid vessel segments with rare or transient RBC flow through them [11]. However, the abnormal TME is associated with marked heterogeneity in haematocrit [12], including reports of plasma-only channels [13].…”
Section: Introductionmentioning
confidence: 99%